EXPORT DEVELOPMENT OF BELARUS - Samakhavets, Maryia; Hrechyshkina, Olena (Quaestiones Geographicae, 2020)
The paper contains a deep analysis of exports of Belarus and defines the proposals for its development. Economic comparisons and systematisation, which is based on the official statistical data for 2012–2018, are used in the study. It is concluded that Belarus exports have a poor diversification; export development is largely determined by Eurasian Economic Union (EAEU) integrating processes; export support of innovative goods and evolution of a single service market through the enhanced cooperation are possible. A generalised model for the export development of innovative goods and services of the EAEU member states on a cooperative basis is proposed.